DRG upcoding in German neonatology - Hendrik Jürges; Juliane Köberlein (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Since 2003/2004, German hospitals are reimbursed based on a prospective payment scheme (diagnosis related groups, DRGs). Patient classification in neonatology is based inter alia on birth weight, with substantial discontinuities in reimbursement at the relevant thresholds. These discontinuities create strong incentives to upcode especially newborns with very low or extremely low birth weight into classes of even lower birth weight. In this paper, we use data from the German birth statistics 1996 to 2010 to document the extent to which German hospitals have upcoded newborns by systematically documenting birth weights below the DRG thresholds. We estimate that between 2003 and 2010, hospitals have gained additional reimbursement in excess of 100 million Euro from the manipulation of birth weights alone. Further, we show that the likelihood of birth weight manipulation may be linked with the strength of financial incentives, regional competition in the hospital sector, ownership status, and newborn health. A corollary of our study is that, for cohorts born after 2002, regression discontinuity designs for effects of neonatal care on child health based on birth weight classifications are invalid.
Keywords: I11; I18; D20; 330